2015
DOI: 10.1080/02724634.2014.948546
|View full text |Cite
|
Sign up to set email alerts
|

Four new Early Devonian ischnacanthid acanthodians from the Mackenzie Mountains, Northwest Territories, Canada: an early experiment in dental diversity

Abstract: The Early Devonian (Lochkovian) Man On The Hill (MOTH) locality in the Northwest Territories has yielded hundreds of exquisitely preserved specimens of over 72 different species of early vertebrates, greatly increasing our understanding of the diversity of this period. In this paper, we describe three new genera comprising four new species of ischnacanthid acanthodian, based on their dentigerous jaw bones and teeth. This taxonomic diversity reflects some of the diversity of dentition found among ischnacanthifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Tightly interlocking teeth have been suggested as an indicator of macrophagy in crocodylians (Young et al 2012), and the anterior and posterior flanges would have formed an almost continuous slicing or cutting surface. The teeth of E. rugosus also have longitudinal ridges (Blais et al 2015), which, in other taxa, have been suggested to indicate the presence of plicidentine (Meunier et al 2014). Plicidentine is currently unknown in ischnacanthiforms, and a histological analysis of the teeth would be required to determine whether these ridges are the result of infolding of the dentine in Euryacanthus.…”
Section: Discussion Trophic Niche Differentiationmentioning
confidence: 99%
See 4 more Smart Citations
“…Tightly interlocking teeth have been suggested as an indicator of macrophagy in crocodylians (Young et al 2012), and the anterior and posterior flanges would have formed an almost continuous slicing or cutting surface. The teeth of E. rugosus also have longitudinal ridges (Blais et al 2015), which, in other taxa, have been suggested to indicate the presence of plicidentine (Meunier et al 2014). Plicidentine is currently unknown in ischnacanthiforms, and a histological analysis of the teeth would be required to determine whether these ridges are the result of infolding of the dentine in Euryacanthus.…”
Section: Discussion Trophic Niche Differentiationmentioning
confidence: 99%
“…To reconstruct the broken teeth and missing jaw cartilage of UALVP 48487, UALVP 45078, and UALVP 41920 were used as references (fig. 5 in Blais et al 2015). The blank labial side of UALVP 45648 was also filled in as flat, as it was reconstructed on the lingual side only and not prepared out of its matrix because of its status as the holotype of the species.…”
Section: X-ray Computed Tomography and Reconstructionmentioning
confidence: 99%
See 3 more Smart Citations